Impact of the SiNx Thickness on Passivation Quality and Contact Resistivity of Silicon Solar Cell - Mojrová, Barbora (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2016)
In this work the influence of thickness of Silicon Nitride (SiNX) layer deposited by Plasma Enhanced Chemical Vapour Deposition (PECVD) on passivation quality and contact resistivity (ρC) of n-type Passivated Emitter Rear Totally-diffused (n-PERT) cell was investigated. The solar cell structure comprises front boron emitter and a phosphorous back surface field (BSF) with SiNX layers on both sides for surface passivation. Contacts are made by screen printed and fired through metallization using commercial silver (Ag) paste.
Keywords: silicon solar cell; n-type; n-PERT; SiNX; passivation; contact resistivity